A Review Article on Detection of Fake Profile on Social-Media (International Journal of Innovative Research in Computer Science & Technology, 2023)
Nowadays, practically everyone, from a  youngster to an adult, spends more time on online social  media platforms, connecting with and exchanging  information with individuals all over the world. The social  network is becoming a popular means to communicate  with people who live in different parts of the world.  Because of the tremendous interconnectedness and  information sharing enabled by the internet, social media  platforms. This highlights the importance of establishing a  system capable of detecting fake profiles on social media  networks. There has been a lot of study done in this area  utilising machine learning algorithms to identify fake  profile, duplicate, spam, and bot accounts, and most of the  fake profile accounts were effectively recognised using  machine learning algorithms. This study discusses fake  profile detection on social networks using machine  learning.
Keywords: Fake Profile; Fake Identities; Security Issues; Social Network Analysis; Machine Learning